Reconstruction as a Catalyst for Security, Stability, and Urban Resilience: A Case Study of Murzuq - Alhodairi, Ahmed; Al-Shareif, Mohamed (Palestine Polytechnic University, 2025)
Cities throughout history have often found themselves at the heart of conflict and disaster, pushing their residents to seek safety elsewhere. Murzuq, a city in southern Libya, has faced its share of hardship since 2019, enduring violent conflict that displaced thousands and left much of its infrastructure in ruins. The destruction not only threatened the safety of its people but also their ability to live and rebuild their lives in their hometown. In 2024, with the establishment of the Libya Reconstruction and Development Fund (LRDF), efforts have been underway to turn the page toward healing, rebuilding, and reimagining the city's future. This research looks into how reconstruction can help bring back a sense of security and stability, using Murzuq as a real-world example. It delves into what has been done so far, what impact those efforts have had, and what can be learned from other global cases. Through descriptive and analytical methods, the study compares the city’s state before and after the intervention. The findings demonstrate a strong connection between reconstruction initiatives and improvements in both safety and resilience. They also shed light on the obstacles that remain and offer pathways for building stronger foundations—especially through collaborative efforts at both the national and local levels aimed at reviving state institutions and restoring basic services.
Number of pages: 9, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Reconstruction, Catalyst, Security, Stability, Urban, Resilience, Case Study, Murzuq